CXCR4 as a Functional Coreceptor for Human Immunodeficiency Virus Type 1 Infection of Primary Macrophages - Simmons, Graham (American Society for Microbiology, 1998)
The coreceptors used by primary syncytium-inducing (SI) human immunodeficiency virus type 1 isolates for infection of primary macrophages were investigated. SI strains using only CXCR4 replicated equally well in macrophages with or without CCR5 and were inhibited by several different ligands for CXCR4 including SDF-1 and bicyclam derivative AMD3100. SI strains that used a broad range of coreceptors including CCR3, CCR5, CCR8, CXCR4, and BONZO infected CCR5-deficient macrophages about 10-fold less efficiently than CCR5(+) macrophages. Moreover, AMD3100 blocked infection of CCR5-negative macrophages by these strains. Our results therefore demonstrate that CXCR4, as well as CCR5, is used for infection of primary macrophages but provide no evidence for the use of alternative coreceptors.